2015
DOI: 10.1007/s00484-015-1028-4
|View full text |Cite
|
Sign up to set email alerts
|

Lagged influence of North Atlantic Oscillation on population dynamics of a Mediterranean terrestrial salamander

Abstract: The North Atlantic Oscillation (NAO) is a largescale climatic pattern that strongly influences the atmospheric circulation in the northern Hemisphere and by consequence the long-term variability of marine and terrestrial ecosystem over great part of northern Europe and western Mediterranean. In the Mediterranean, the effects of the NAO on vertebrates has been studied mainly on bird populations but was rarely analysed in ectothermic animals, and in particular in amphibians. In this study, we investigated the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
7
1
Order By: Relevance
“…High detection probability has already been demonstrated in other species of cave salamanders, particularly during their underground activity phase 5 , 47 49 , and this favors studies on the ecology and dynamics of cave salamander populations (e.g. 39 , 48 , 49 ). The match between mixture models and removal sampling was excellent for the caves with fewer salamanders.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…High detection probability has already been demonstrated in other species of cave salamanders, particularly during their underground activity phase 5 , 47 49 , and this favors studies on the ecology and dynamics of cave salamander populations (e.g. 39 , 48 , 49 ). The match between mixture models and removal sampling was excellent for the caves with fewer salamanders.…”
Section: Discussionmentioning
confidence: 90%
“…It is well known that salamander populations can undergo strong temporal variation, for instance in response to habitat modifications, climatic variation and variation of biotic factors (e.g. 7 , 39 , 40 ), and population fluctuations can occur even in absence of evident habitat changes 41 . Despite we do not have quantitative data on population dynamics, the available information suggests that the study populations did not undergo strong variations of abundance through time.…”
Section: Discussionmentioning
confidence: 99%
“…In the past two decades, a growing number of studies have shown that the NAO influences abundance and demographic parameters in several taxa, including birds (e.g., Nevoux, Barbraud, & Barbraud, ), mammals (e.g., Post & Stenseth, ), amphibians (Salvidio, Oneto, Ottonello, & Pastorino, ), and fishes (e.g., Attrill & Power, ). In mammals and birds, the NAO has varying effects on survival, sometimes in combination with other environmental factors (e.g., level of food resources, predation) or with internal state variables (e.g., age, sex) (Coulson et al., ; Payo‐Payo, Genovart, Bertolero, Pradel, & Oro, ; Pokallus & Pauli, ).…”
Section: Introductionmentioning
confidence: 99%
“…Literature data provide a number of examples on how autumn and winter temperature affect amphibians, from positive effects of higher temperatures on the agile frog (Combes et al 2018) to negative ones for B. bufo (Reading and Clarke 1995;Reading 2007). The positive influence of autumn and winter precipitation on amphibian populations was documented in a few research projects (Jensen et al 2003;Hartel 2008a;Cayuela et al 2014;Benard 2015;Salvidio et al 2016;Combes et al 2018) and higher humidity should decrease desiccation risks during hibernation (Combes et al 2018). In this study, we revealed a trend towards an increase in winter humidity over the years of monitoring, while temperature variation patterns seemed random.…”
Section: Discussionmentioning
confidence: 99%